Gambaran kejadian demam berdarah dengue - Rufiana, Khusnul Rohim; Arifah, Siti; Nuryati, Nuryati (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Dengue Hemorrhagic Fever (DHF) is an infectious disease characterized by changes in platelet and hematocrit levels, especially in the critical phase. Purpose: To analyze patient characteristics, signs and symptoms, and laboratory test results in DHF patients. Method: A case study design was conducted at a hospital in Central Java in September. A total of 5 children with Dengue Hemorrhagic Fever (DHF) were recruited by accidental sampling with the criteria of children who had been diagnosed with Dengue Hemorrhagic Fever (DHF) by doctors who were participants in this study. Results: There were more male patients than female patients, with the largest age range being 14-15 years. The most common length of hospitalization was 5 days (80%). The most common symptoms were decreased platelets (<150.000), hematocrit (<38%) and leukocytes (<4.400), while bleeding occurred more often on the 4th and 5th days. The critical phase is characterized by the highest decrease in platelets on day 7 and an increase in hematocrit on day 5, which increases the risk of plasma leakage and shock. A sudden decrease in body temperature is an important indicator in recognizing the critical phase. Conclusion: The most common clinical symptoms found in patients are decreased platelets and leukocytes, while other symptoms such as bleeding, nausea, vomiting, and pain vary. In addition to clinical factors, the level of public knowledge about DHF is relatively good, but the implementation of preventive measures is still low. This indicates the need for more intensive education and community-based interventions to increase awareness and behavioral changes in preventing DHF. Keywords: Dengue Hemorrhagic Fever; Critical Phase; Thrombocytopenia; Hematocrit; Patient Characteristics Pendahuluan: Demam Berdarah Dengue (DBD) merupakan penyakit infeksi yang ditandai dengan perubahan kadar trombosit dan hematokrit, terutama pada fase kritis. Tujuan: Untuk menganalisis karakteristik pasien, tanda dan gejala, serta hasil pemeriksaan laboratorium pada pasien DBD. Metode: Penelitian dengan rancangan studi kasus yang dilakukan di sebuah rumah sakit di Jawa Tengah pada bulan September. Diperoleh sebanyak 5 anak dengan Dengue Hemorrhagic Fever (DHF) direkrut dengan cara accidental sampling dengan kriteria anak-anak yang telah didiagnosis Dengue Hemorrhagic Fever (DHF) oleh dokter yang menjadi partisipan dalam penelitian ini. Hasil: Pasien laki-laki lebih banyak dibandingkan perempuan, dengan rentang usia terbanyak 14-15 tahun. Lama rawat inap paling umum adalah 5 hari (80%). Gejala yang paling sering muncul adalah penurunan trombosit (<150.000), hematokrit (<38%) dan leukosit (<4.400), sementara perdarahan lebih sering terjadi pada hari ke-4 dan ke-5. Fase kritis ditandai dengan penurunan trombosit tertinggi pada hari ke-7 dan peningkatan hematokrit pada hari ke-5, yang meningkatkan risiko kebocoran plasma dan syok. Penurunan mendadak suhu tubuh menjadi indikator penting dalam mengenali fase kritis. Simpulan: Gejala klinis yang paling umum ditemukan pada pasien adalah penurunan trombosit dan leukosit, sedangkan gejala lain seperti perdarahan, mual, muntah, dan nyeri bersifat bervariasi. Selain faktor klinis, tingkat pengetahuan masyarakat tentang DBD tergolong baik, tetapi penerapan tindakan pencegahan masih rendah. Hal ini menunjukkan perlunya edukasi yang lebih intensif dan intervensi berbasis komunitas untuk meningkatkan kesadaran serta perubahan perilaku dalam mencegah DBD. Kata Kunci: Demam Berdarah Dengue; Fase Kritis; Trombositopenia; Hematokrit; Karakteristik Pasien